Flexibility of Knee Joint Muscles in Women with Knee Osteoarthritis and Healthy Controls - Sara Abolahrari Shirazi; Farahnaz Ghafari Nezhad; Maryam Ebrahimian; Elham Nouraddini; Azadeh Mansoorian; Farahnaz Emami (Shiraz University of Medical Sciences, 2015)
Background: Osteoarthritis is one of the most common diseases in synovial joints. Due to high loading forces during weight-bearing activities, the knee joint is prone to degenerative processes. This study aimed to compare the flexibility of muscles around the knee joint in patients with knee osteoarthritis with those of healthy individuals. Methods: Twenty-three women with bilateral knee osteoarthritis and 23 healthy women matched with the patient group for age, height and weight participated in this study. Flexibility of the quadriceps, hamstring, iliotibial band, adductor and gastrocnemius muscles was evaluated with a goniometric device. Pain intensity was assessed with a visual analogue scale. The data were analyzed with independent t-tests to compare the two groups, and Pearson correlation coefficient was calculated to correlate muscle flexibility and pain intensity. Results: significant lower flexibility of the bilateral quadriceps muscles was found in patients compared to healthy women (P<0.05). No significant differences were detected between groups regarding other muscles. Quadriceps flexibility correlated significantly with pain intensity in patients (P<0.001). Conclusion: In patients with osteoarthritis, quadriceps flexibility may be decreased although other muscles may remain unaffected. Quadriceps stretching is thus a potentially important component of treatment, which may influence pain reduction in these patients.